HUBUNGAN KONSEP DIRI AKADEMIK DENGAN EFIKASI DIRI PADA SISWA SMA N 17 TEBO - Utami, Sri; Rasimin, Rasimin; Zubaidah, Zubaidah (Universitas Islam Kalimantan Muhammad Arsyad Al-Banjari Banjarmasin, 2024)
This research aims to find out what academic self-concept, self-efficacy is and the relationship between academic self-concept and student self-efficacy at SMA Negeri 17 Tebo using quantitative methods through a correlational approach with Pearson Product Moment correlation analysis. This research took 84 respondents from SMA Negeri 17 Tebo students. The results of the research show that there is a relationship between academic self-concept and student self-efficacy at SMA Negeri 17 Tebo. The research results show a correlation of 0.610, which means the relationship can be categorized as a moderate correlation or a sufficient relationship. Based on this research, it is hoped that future researchers will study and deepen their insight into academic self-efficacy and self-concept so that they will be able to get better or maximum results. Apart from that, it is hoped that guidance and counseling teachers can provide encouragement in the form of trust and self-confidence in students to help improve good learning outcomes.